Could Commoning Unlock the Potential of Integrated Landscape Approaches? - Xiao Lu Wang; Wai Fung Lam (Land)
Background: Landscape approaches are recognized for their holistic view on development and conservation. However, they encounter sustainability and localization challenges due to short-term funding constraints and dependence on external experts. In this paper, we examine commoning as a means of land tenure interventions that enable mixed land use and community stewardship. Methods: Based on desk research and 20 interviews, an institutional analysis was performed on two landscape management cases to shed light on commoning processes and land tenure changes, as well as their impact on land use and community stewardship. Results: In the first case, a collaborative governance model was developed through policy interventions, which provided not only institutional frameworks but also financial resources to incentivize landowners to cooperate with nature conservation groups and share management rights over their land. In the second case, a community land trust model was used by self-organized civil society actors to develop ecovillage practices and ensure the balance of conservation and agricultural uses. In both cases, we found that land tenure innovations in terms of boundary rules, choice rules, aggregation rules, as well as rules for higher-level action situations, were key to enabling land rights sharing, mixed land use, and different levels of stewardship depending on the preferences and capacity of stakeholders. Conclusions: Commoning could address the sustainability and localization challenges faced by landscape approaches to mixed land use and long-term adaptive management.